1986
DOI: 10.1073/pnas.83.3.797
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and comparison of repeated DNA sequences from the human filarial parasite Brugia malayi and the animal parasite Brugia pahangi.

Abstract: A 320-base-pair repeated sequence was observed when DNA samples from the filarial parasites Brugia malayi and Brugia pahangi were digested with the restriction endonuclease Hha I. A 640-base-pair dimer of the repeated sequence from B. malayi was inserted into the plasmid pBR322. When dot hybridization was used, the copy number of the repeat in B. malayi was found to be about 30,000. The 320-base-pair Hha I repeated sequences are arranged in direct tandem arrays and comprise about 12% of the genome. B. pahangi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 23 publications
0
56
0
1
Order By: Relevance
“…The present study shows that this sequence is also a useful target for real-time PCR. Early studies estimated that there were about 30,000 copies of the HhaI repeat per haploid genome of B. malayi (ϳ10% of the total DNA) (20). Shotgun sequencing of the B. malayi genome has shown that the HhaI repeat is less abundant than this and suggests that the HhaI repeat comprises only ϳ1% of the haploid genome (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study shows that this sequence is also a useful target for real-time PCR. Early studies estimated that there were about 30,000 copies of the HhaI repeat per haploid genome of B. malayi (ϳ10% of the total DNA) (20). Shotgun sequencing of the B. malayi genome has shown that the HhaI repeat is less abundant than this and suggests that the HhaI repeat comprises only ϳ1% of the haploid genome (7).…”
Section: Discussionmentioning
confidence: 99%
“…A control plasmid was constructed by cloning a PCR product of the B. malayi HhaI repeat (20) into the pCR4-TOPO vector (Invitrogen, Carlsbad, CA), according to the manufacturer's instructions. The plasmid was propagated in Escherichia coli and purified by using a QIAprep spin miniprep kit (QIAGEN, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, hybridization of parasite DNA obtained from a patient or a suspected animal reservoir will definitively identify the organism for which the probe is specific, while ruling out other species. For example, species-specific probes have been generated for Brugia malayi (McReynolds, DeSimone & Williams, 1986;Sim, Mak, Cheong, Sutanto, Kurniawan, Marwoto, Franke, Campell, Wirth & Peissens, 1986;Sim, Piessens & Wirth, 1986) and Onchocerca volvulus (Perler & Karam, 1986); for the latter, a strain-specific probe, able to distinguish between forest and Savannah forms, has recently been reported (Ertmann, Unnasch, Greene, Albiez, Boateng, Denke, Ferraroni, Karam, Schulz-Key & Williams, 1987). The alternative approach is to generate probes that hybridize with the DNA of all filarial parasites, but can distinguish between the DNA of various parasites on the basis of restriction fragment length polymorphisms (RFLPs).…”
Section: Introductionmentioning
confidence: 99%
“…So far no sequence consistent differences of the Hha I repeat in different strains of B. malayi have been found and it was reported that the Hha I repeat of B. malayi is species specific and distinct from that of the closely related species B. pahangi. 20 Since the Hha I sequence is highly repeated and comprises about 13% of the whole B. malayi genome, this sequence appears to be preordained as PCR target for the development of specific and sensitive detection assays for this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we developed a PCR-ELISA method based on the Hha I repeat of B. malayi, 20 which involves the coamplification of an internal control. This method was evaluated on blood samples from persons living in an area endemic for nocturnally periodic B. malayi in central Sulawesi, Indonesia.…”
mentioning
confidence: 99%